Compiling, verifying and simulating dynamic software architectures using ANTLR and coloured-ADL. (2017) - Mokhtari, Rabah; Chaoui, Allaoua
The concept of reconfigurable and dynamic software architecture (DSA) occupies today an important place in the field of software engineering. As result, several architecture description languages (ADLs) and approaches have been proposed for describing DSA in the highest level of abstraction. However, most of these works present theoretical solutions without giving an idea on the execution of final systems at run time. In this paper, we propose a new DSA called coloured software architecture (CSA) based on two concepts coloured operation and coloured connector. Then, we propose a new ADL called coloured-ADL and implement a compiling, verification and simulation tool dedicated to CSA. The simulation of system instances, derived from a CSA, is mainly used to explain coloured-ADL and evaluate the reliability of the simulated system. On the other hand, the verification is focused on checking a new defined safety property called architectural stack overflow (ASO). A safe CSA should be free of ASO violation property. To check a CSA, the verification uses also finite state processes (FSP) and labelled transition state (LTS) to expect this kind of property. We illustrate our propositions through two case studies from the literature.